Impacto do barramento de um rio amazônico sobre os padrões de sincronia de grupos funcionais fitoplanctônicos. - Campos, Beatriz Melissa (2022)
The degree at which populations are correlated in space is called spatial synchrony and can be affected by interspecific interactions, dispersion, and large-scale environmental factors, i. e. Moran effect. The study of this phenomenon can help understanding the temporal stability of communities and the underlying mechanisms. The influence of damming in a river from the Amazon basin (Santo Antônio do Jari HPP) on the synchrony of the environment and the phytoplankton community was evaluated, both for the total density and for different Reynolds functional groups. Was investigated whether the effects would be similar for the main channel (Jari River), tributaries, and for the total area (Jari + tributaries). The mean synchrony values and the confidence intervals of each abiotic variable, functional group, and the total density were estimated for the total area, Jari River and tributaries. Matrix-based multiple regression were also performed to identify the most important drivers of synchrony of the phytoplankton. Changes in the synchrony patterns were verified after the damming. The temporal dynamics of environmental variables, total density and of some functional groups was more synchronous when considering only the Jari River, than the total area or only tributaries. Environmental synchrony and environmental distance were the main mechanisms behind synchrony for some functional groups.